The Etiology and Clinical Course of Chronic Pancreatitis in Children With Early Onset of the Disease. Issue 6 (December 2016) - Wejnarska, Karolina; Kolodziejczyk, Elwira; Wertheim-Tysarowska, Katarzyna; Dadalski, Maciej; Sobczynska-Tomaszewska, Agnieszka; Kierkus, Jarosław; Bal, Jerzy; Rygiel, Agnieszka Magdalena; Oracz, Grzegorz
ABSTRACT: Objectives: The etiological factors of chronic pancreatitis (CP) in children differ from those in adults. To date, no study has assessed the clinical course of CP in young children. The aim of our study was to evaluate the etiology and the clinical presentation of the disease in children with disease onset before 5 years of age in comparison to later-onset of CP. Methods: A total of 276 children with CP, hospitalized from 1988 to 2015, were enrolled in the study. Data on presentation, diagnostic findings, and treatment were reviewed. Two hundred sixty patients were screened for the most frequent mutations in major pancreatitis-associated genes, such as cationic trypsinogen/serine protease gene ( PRSS1 ), serine protease inhibitor, Kazal type 1 gene ( SPINK1 ), and cystic fibrosis transmembrane conductance regulator gene ( CFTR ). Results: The disease onset before the age of 5 years occurred in 51 patients (group 1), the later onset in 225 patients (group 2). We found no significant discrepancies in distribution of the etiological factors between groups. The youngest patients (group 1) had more pancreatitis episodes (median 5.0 vs 3.00; P  < 0.05) and underwent surgeries more frequently (25.5% vs 8.9%; P  < 0.05). It could be associated with significantly longer follow-up in early onset group (median 6 vs 4 years; P  < 0.05). There were no differences in nutritional status or exocrine and endocrine pancreatic function. Conclusions: Early- and later-onset pancreatitis have similar etiological factors with predominance of gene mutations. The most frequent mutation found was p.Asn34Ser (N34S) in SPINK1 gene. The clinical presentation differed in number of pancreatitis episodes and frequency of surgeries. Abstract : Supplemental Digital Content is available in the text